0177 Bovine macrophage phenotype influences inflammatory response to lipopolysaccharide. (1st October 2016) - Raphael, W.; Contreras, G. A.
Abstract: Severe inflammation during gram negative bacterial disease is common in periparturient dairy cows and increases the severity of diseases such as Escherichia coli mastitis. Tissue inflammation is partly orchestrated by macrophage responses to bacterial infection. Studies in monogastric species showed classical phenotype macrophages have proinflammatory responses and alternative phenotype macrophages have protective and restorative responses during disease. However, responses of diverse bovine macrophage phenotypes to lipopolysaccharide are unclear. The objective of this research was to compare the lipopolysaccharide-induced inflammatory response in several phenotypes of bovine primary monocyte-derived macrophages. Peripheral blood mononuclear cells were isolated from whole blood using Ficoll ( n = 8 cows). Monocytes were identified using mouse anti-bovine CD172α monoclonal antibody and separated from lymphocytes using magnetic assisted cell sorting. Monocytes were cultured with interferon-γ or interleukins (IL) 4 and 13 to induce a classical or alternative macrophage phenotype, respectively, then stimulated with lipopolysaccharide. Macrophage mRNA was quantified in adipose using qPCR. Fold changes in mRNA concentration were calculated by 2 -ΔΔCt, using the untreated cells as calibrator and three endogenous control mRNA. Treatment differences in mRNA expression were identified using Fisher pairwise comparisons and ANOVA ( P ≤ 0.05). Flow cytometry showed magnetic assisted cell sorting increased CD172α + cells from 22.3 ± 1.9 to 81.6 ± 2.8%. After 48 h in vitro, CD68 expression increased and CD172α + was 95.2 ± 0.4%. Lipopolysaccharide increased IL6, IL10, TNF, and CCL2 expression. Lipopolysaccharide stimulated IL6 and IL10 expression was decreased in alternative macrophages, whereas lipopolysaccharide stimulated TNF expression was increased in classical macrophages. Lipopolysaccharide stimulated CCL2 expression was not different between macrophage types. Together these results show an exacerbated proinflammatory cytokine profile in a model of classical bovine macrophages during gram negative bacterial disease. Results suggest that macrophage phenotype could be involved with severe inflammatory responses seen during dairy cow periparturient periods characterized by prolonged and exacerbated lipolysis and increased disease susceptibility. Ongoing research will describe macrophage phenotype during bovine disease and identify factors contributing to phenotype change. Such factors could ultimately be manipulated to control the bovine macrophage inflammatory response.